A Framework of Legal Factors for Human Resource Management - Mohammed A. Abu Rumman (International Journal of Supply Chain Management, 2022)
Legislative body and judicial ruling enrols the law for human resource management, this law is generally refereed as legal context. It is quite comprehensive and complex context. It is applicable for handling the discrimination of employment and labours. This paper presents the detail of legal context of administration of law in the Jordan country . It also studies and compare law system with other countries. This research concentrates on the validity standards and laws which are used in legal context. Features of ethics and privacy related to the human resource management is discussed. Impact of Tax regulation and law are reviewed. Emergency issues which includes applicant and employee relations were studied. Ethics which deals with employee compensation is then discussed. Finally the influence of legal system on policies and practices of human resource management is analysed.